Semi‐rational Engineering of a Promiscuous Fatty Acid Hydratase for Alteration of Regioselectivity. (30th December 2021) - Zhang, Yan; Breum, Niels Mikkel Dyrby; Schubert, Sune; Hashemi, Negin; Kyhnau, Rikke; Knauf, Marius Sandholt; Mathialakan, Masuthan; Takeuchi, Michiki; Kishino, Shigenobu; Ogawa, Jun; Kristensen, Peter; Guo, Zheng; et al.
Abstract: Fatty acid hydratases (FAHs) catalyze regio‐ and stereo‐selective hydration of unsaturated fatty acids to produce hydroxy fatty acids. Fatty acid hydratase‐1 (FA‐HY1) from Lactobacillus Acidophilus is the most promiscuous and regiodiverse FAH identified so far. Here, we engineered binding site residues of FA‐HY1 (S393, S395, S218 and P380) by semi‐rational protein engineering to alter regioselectivity. Although it was not possible to obtain a completely new type of regioselectivity with our mutant libraries, a significant shift of regioselectivity was observed towards cis ‐5, cis ‐8, cis ‐11, cis ‐14, cis ‐17‐eicosapentaenoic acid (EPA). We identified mutants (S393/S395 mutants) with excellent regioselectivity, generating a single hydroxy fatty acid product from EPA (15‐OH product), which is advantageous from application perspective. This result is impressive given that wild‐type FA‐HY1 produces a mixture of 12‐OH and 15‐OH products at 63 : 37 ratio (12‐OH : 15‐OH). Moreover, our results indicate that native FA‐HY1 is at its limit in terms of promiscuity and regiospecificity, thus it may not be possible to diversify its product portfolio with active site engineering. This behavior of FA‐HY1 is unlike its orthologue, fatty acid hydratase‐2 (FA‐HY2; 58 % sequence identity to FA‐HY1), which has been shown earlier to exhibit significant promiscuity and regioselectivity changes by a few active site mutations. Our reverse engineering from FA‐HY1 to FA‐HY2 further demonstrates this conclusion. Abstract : A semi‐rational mutant library of a promiscuous fatty acid hydrtatase (FA‐HY1) revealed several mutants, which exhibited an impressive shift of regioselectivity towards eicosapentaenoic acid (EPA) substrate. While the wild‐type enzyme produces a mixture of two hydroxy fatty acid regioisomers at a ratio of 63 : 37 (12‐OH : 15‐OH), six mutants were able to form exclusively a single hydroxy fatty acid regioisomer (15‐OH).